AN EVALUATION OF DEFERRED TIME-OUT TO TREAT NONCOMPLIANCE IN THE CLASSROOM SETTING - Buzenski, Jessica M. (East Carolina University, 2017)
Time-out (TO) is a widely recommended behavioral management strategy that has been minimally researched in regards to its components and applications or training procedures for teachers (Ryan et al., 2007; Sterling-Turner & Watson, 1999). There is no published evidence for the use of direct training procedures to implement TO in the general classroom setting. Deferred time-out (DTO) is a specific TO training procedure developed to increase compliant behavior in children who were not responsive to the traditional TO strategy (Warzak & Floress, 2009). By providing consultative training, a specific TO procedure to follow, and adding the deferment component, DTO has the potential to increase TO effectiveness in the classroom setting. A multiple baseline design across participants was used to assess disruptive behavior, latency of compliance, and teacher acceptability of DTO procedures in the classroom. Overall, results indicate that the intervention was successful in reducing disruptive behavior for all three students and there were noted decreases in latency between when the DTO instruction was given and when the student initiated the TO. Additionally, teacher responses on acceptability measures indicated high social validity. Using procedures such as DTO to decrease disruptive behaviors allows for improved social functioning and increased educational time with better learning opportunities, not only for the target student, but the classroom as whole.
Keywords: disruptive behavior; deferred; classroom; single case design; multiple baseline; Classroom management; Timeout method